MISI DALAM MASYARAKAT MAJEMUK - Megawati Manullang (Jurnal Teologi Cultivation, 2019)
AbstractThis paper tells about mission which doing in the different condition. Thedifferent is explained in this paper are about race, gender, skin color,language and religion. Religious diversity is about how if the mission isstated in the sensitivity of different without give rise to problem and conflict. There is challenge when doing the Jesus‟s mission in Indonesia which have religious diversity. When we talk about the truth of Jesus, we preface to the condition of religion pluralism. The data is using in this paper rise up from the method. The method is library studying. The presentation of the material is using by bible‟s study analysis.Keywords: Mission, Pluralism